Preterm infants' first breastfeeding attempt: Early initiation and performance: A large multicentre questionnaire study based on maternal observations. - Ragnhild Maastrup; Sisse Walloee; Hanne Kronborg; Helle B Sandfeld; Ane L Rom (PLoS ONE, 2025)
The Baby-friendly Hospital Initiative for neonatal wards and the World Health Organization recommend that stable preterm infants initiate breastfeeding regardless of gestational age, postmenstrual age (PMA), or weight. Documented practice, however, is limited. We aimed to describe PMA at first breastfeeding attempt of stable preterm infants, to analyse delaying factors, to detect differences in breastfeeding performance across gestational age groups and use of nasal-CPAP. This Danish multicentre cohort study was based on questionnaires answered by mothers of 992 preterm infants gestational age 23-36 weeks. Differences in PMA between gestational age groups at first breastfeeding attempt were analysed by One-way ANOVA, and associations between PMA and selected factors by linear regression models. The lowest PMA at first breastfeeding attempt was 27.57 weeks. Of the extremely and very preterm infants, 61% and 46%, respectively, had the first breastfeeding attempt before PMA 32 weeks. Mechanical ventilation significantly delayed first breastfeeding attempt by seven days (p < 0.0001). Performance at the preterm infants' first breastfeeding attempt were predominantly without swallowing (78%). During first attempt, 29% were at breast with nasal-CPAP. Performance was in general not affected by nasal-CPAP treatment. In this cohort of preterm infants, we conclude that early initiation of breastfeeding is possible, also at low PMA and while maintained on nasal-CPAP. Hence, nasal-CPAP should not be a barrier for breastfeeding initiation. At first breastfeeding, even preterm infants before PMA 32 weeks demonstrated breastfeeding behaviours, although the majority did not swallow. Preterm infants need time to familiarize with the breast.